2017
DOI: 10.1371/journal.pone.0175467
|View full text |Cite
|
Sign up to set email alerts
|

Growth deficits in cystic fibrosis mice begin in utero prior to IGF-1 reduction

Abstract: Growth deficits are common in cystic fibrosis (CF), but their cause is complex, with contributions from exocrine pancreatic insufficiency, pulmonary complications, gastrointestinal obstructions, and endocrine abnormalities. The CF mouse model displays similar growth impairment despite exocrine pancreatic function and in the absence of chronic pulmonary infection. The high incidence of intestinal obstruction in the CF mouse has been suggested to significantly contribute to the observed growth deficits. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…It has been observed that IGF-1, as well as insulin, stimulates NO production in endothelial cells [96]. In CF mice, IGF-1 reduction was seen in late adolescence and reduced weight and length occurred independent of gastrointestinal CF issues [97]. As chronic inflammation in CF patients could lower IGF-1 concentration, NO production could be influenced as well as the possibility that respiratory impairment might rise as IGF-1 levels decrease [98].…”
Section: Arg/no Metabolism In Nutritional Failurementioning
confidence: 99%
“…It has been observed that IGF-1, as well as insulin, stimulates NO production in endothelial cells [96]. In CF mice, IGF-1 reduction was seen in late adolescence and reduced weight and length occurred independent of gastrointestinal CF issues [97]. As chronic inflammation in CF patients could lower IGF-1 concentration, NO production could be influenced as well as the possibility that respiratory impairment might rise as IGF-1 levels decrease [98].…”
Section: Arg/no Metabolism In Nutritional Failurementioning
confidence: 99%
“…Of note, there were no differences in IGF-1 levels in late gestation or at birth; levels of CF mice did not diverge from control mice until 3 weeks’ postnatal age 14. Thus, while reductions in IGF-1 in CF are observed among humans, pigs and mice, the timing of these changes is not necessarily consistent between humans and various animal models.…”
mentioning
confidence: 83%
“…In CF mice and also in a Cftr invfl10 +villin-Cre mice (a model with correctable intestinal obstruction), adult CF mice had lower IGF-1 compared with wild-type littermates; these lower IGF-1 levels were correlated with decreased weight and length 14. Of note, there were no differences in IGF-1 levels in late gestation or at birth; levels of CF mice did not diverge from control mice until 3 weeks’ postnatal age 14.…”
mentioning
confidence: 91%
See 2 more Smart Citations